Dynamic ultrasound molecular‐targeted imaging of senescence in evaluation of lapatinib resistance in HER2‐positive breast cancer - Xiaoyu Chen; Ying Li; Zhiwei Zhou; Yanqiu Zhang; Luchen Chang; Xiujun Gao; Qing Li; Hao Luo; Kenneth D. Westover; Jialin Zhu; Xi Wei (Cancer Medicine, 2023)
Abstract Background Prolonged treatment of HER2+ breast cancer with lapatinib (LAP) causes cellular senescence and acquired drug resistance, which often associating with poor prognosis for patients. We aim to explore the correlation between cellular senescence and LAP resistance in HER2+ breast cancer, screen for molecular marker of reversible senescence, and construct targeted nanobubbles for ultrasound molecular imaging to dynamically evaluate LAP resistance. Methods and Results In this study, we established a new cellular model of reversible cellular senescence using LAP and HER2+ breast cancer cells and found that reversible senescence contributed to LAP resistance in HER2+ breast cancer. Then, we identified ecto‐5′‐nucleotidase (NT5E) as a marker of reversible senescence in HER2+ breast cancer. Based on this, we constructed NT5E‐targeted nanobubbles (NT5E‐FITC‐NBs) as a new molecular imaging modality which could both target reversible senescent cells and be used for ultrasound imaging. NT5E‐FITC‐NBs showed excellent physical and imaging characteristics. As an ultrasound contrast agent, NT5E‐FITC‐NBs could accurately identify reversible senescent cells both in vitro and in vivo. Conclusions Our data demonstrate that cellular senescence‐based ultrasound‐targeted imaging can identify reversible senescence and evaluate LAP resistance effectively in HER2+ breast cancer cells, which has the potential to improve cancer treatment outcomes by altering therapeutic strategies ahead of aggressive recurrences.